Technology Based Motivation Strategies To Improve Employee Performance In The Digital Era - Salsabila Azizah; Sri Mayang Mandra; Salfen Hasri; Sohiron (Journal of Practice Learning and Educational Development, 2025)
This study aims to explore technology-based motivation strategies in enhancing employee performance, particularly in the digital era and within the context of Islamic educational institutions. Using a library research approach and reviewing the latest academic sources, the findings reveal that digital tools such as performance dashboards, e-reward platforms, and online evaluation systems can significantly improve employees' intrinsic motivation and work ethics. These strategies are reinforced by motivation theories such as expectancy theory (Vroom) and goal-setting theory (Locke & Latham), and contextualized with Islamic values including amanah (trust), muhasabah (self-evaluation), and uswah hasanah (exemplary leadership). Digital work systems not only improve efficiency but can also function as spiritual instruments that strengthen sincerity and intention in work. This study implies that digital transformation must be framed within ethical and spiritual values to ensure meaningful and humane work motivation.